Pengembangan Profesionalisme Guru di Kabupaten Hulu Sungai Utara (Studi Kasus di SDN Rantau Karau Tengah dan SDN Rantau Karau Hilir) - Fikri, Muhammad; Hadi, Sutarto; Saleh, Muhammad (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Education is a conscious effort made to prepare human resources to be able to participate actively in society. Good education is expected to give birth to a superior generation that can continue the development and progress of a nation. Quality education is determined, among other things, by the presence of quality teachers, namely teachers who can carry out their responsibilities professionally. Professional teachers have at least four competencies, namely pedagogic, personality, social and professional competencies. Developing teacher professionalism is a continuous effort made to ensure the quality of education and learning in schools. Teacher professionalism development takes place at three levels, namely personal, institutional and government. The implementation of teacher professionalism development is still problematic in several regions, especially considering the low quality of education. The results of international comparative studies such as TIMSS and PISA place Indonesia in the lowest position. This research aims to find out how teacher professionalism is developed in North Hulu Sungai Regency. This research uses a case study strategy at SDN Rantau Karau Tengah and SDN Rantau Karau Hilir. The results of the research show that, at both SDN Rantau Karau Tengah and SDN Rantau Karau Hilir, the majority of teachers have a bachelor's education certificate, which is the minimum requirement as a teacher, and the majority of teachers have a certificate as a professional teacher. The development of teacher professionalism in North Hulu Sungai Regency occurs at all levels, namely the personal, institutional and government levels. In terms of participation in teacher professional development programs, the two SDNs differ quite significantly. Teachers at SDN Rantau Karau Hilir generally have participated in training carried out by the government, while teachers at SDN Rantau Karau Tengah are less involved in scientific activities, such as seminars and the like, are diligent in participating in teacher achievement competitions, and feel that the District Government provides assistance. towards increasing their professionalism. Meanwhile, teachers at SDN Rantau Karau Tengah are not always involved in scientific activities, rarely take part in achievement teacher competitions, and feel that the District Government does not contribute to increasing their professionalism.